2017
DOI: 10.1007/978-3-319-66182-7_50
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Hyper-connectivity Networks for MCI Classification

Abstract: Hyper-connectivity network is a network where every edge is connected to more than two nodes, and can be naturally denoted using a hyper-graph. Hyper-connectivity brain network, either based on structural or functional interactions among the brain regions, has been used for brain disease diagnosis. However, the conventional hyper-connectivity network is constructed solely based on single modality data, ignoring potential complementary information conveyed by other modalities. The integration of complementary i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Network construction is critical for the classification of brain networks based on hypergraphs. Hypernetwork construction methods have been proposed previous publications; however, most of the existing functional hypernetwork models were characterized by the interaction of multi-regions in a static form ( Jie et al, 2016 ; Li et al, 2017 ; Zu et al, 2018 ; Li Y. et al, 2019 ). However, research has shown that even in the resting state, brain neural activity still reveals transient and subtle dynamic changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Network construction is critical for the classification of brain networks based on hypergraphs. Hypernetwork construction methods have been proposed previous publications; however, most of the existing functional hypernetwork models were characterized by the interaction of multi-regions in a static form ( Jie et al, 2016 ; Li et al, 2017 ; Zu et al, 2018 ; Li Y. et al, 2019 ). However, research has shown that even in the resting state, brain neural activity still reveals transient and subtle dynamic changes.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Jie et al (2016) used the Least absolute shrinkage and selection operator (LASSO) method to create a hyper-network model and applied this to the diagnosis of brain diseases. In another study, Yang et al ( Li et al, 2017 ) adopted the star expansion method to construct structural hyper-networks and functional hyper-networks, respectively, to then perform classification analysis. Taking into account the group effecting problem within brain networks, Guo et al (2018a) proposed the elastic net and group LASSO method to improve the establishment of hyper-network models to facilitate brain disease classification research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-kernel SVM has been used to classify patients with AD and NCs [93]. Subsequent studies have improved these methods and proposed multimodal hypernetwork modeling techniques that leverage the richer information present in multimodal data [94][95][96]. Moreover, hypergraphs have been used to identify connectivity relationships and optimize the weights of hyperedges, to better represent the relationships among brain regions [97,98].…”
Section: Classificationmentioning
confidence: 99%